"Sign Me Up, I'm Ready!": Helping Patients Prescribed Sleeping Medication Engage with Cognitive Behavioral Therapy for Insomnia (CBT-I). Issue 5 (3rd September 2021) - Koffel, Erin; Branson, Mariah; Amundson, Erin; Wisdom, Jennifer P.
ABSTRACT: Objective/Background: Cognitive behavioral therapy for insomnia (CBT-I) provides safe and effective insomnia care without the risk of harm associated with sleeping medications. Unfortunately, few patients with insomnia engage with CBT-I, with most using sedative hypnotics instead. This study conducted focus groups with patients with insomnia who were treated with sleeping medication, including older adults, women, and patients with chronic pain. The goal was to explore the perspectives of high-risk, CBT-I naïve patients on increasing access and engagement with CBT-I. Participants: Participants included 29 Veterans with insomnia who had been prescribed sleeping medication in the last year and had not previously engaged with CBT-I. Methods: Semi-structured 90-min focus groups were used to 1) explore messages and appropriate channels for a CBT-I social marketing campaign, 2) determine patient preferences for self-management CBT-I tools, and 3) determine patient opinions on alternative provider-delivered forms of CBT-I. Thematic analysis was used to identify conceptual themes. Results: Three main themes were identified. First, patient education is necessary but not sufficient. Patients recommended multiple outreach attempts through multiple channels to motivate tired and overwhelmed insomnia patients to engage with CBT-I. Second, patients gravitated toward a stepped-care approach. Most would start with self-management CBT-I tools, moving on to provider-delivered CBT-I if needed. Finally, patients appreciated being able to choose from a menu of CBT-I delivery options and would use multiple options simultaneously. Conclusions: These findings suggest promising opportunities to increase the use of CBT-I for high-risk patients through patient education and provision of self-management CBT-I tools.